Oxygen Self‐Supply Engineering‐Ferritin for the Relief of Hypoxia in Tumors and the Enhancement of Photodynamic Therapy Efficacy. Issue 15 (25th February 2022) - Zhu, Yang; Jin, Duo; Liu, Manman; Dai, Yi; Li, Li; Zheng, Xinwei; Wang, Lulu; Shen, Aizong; Yu, Jianing; Wu, Sisi; Wu, Yun; Zhong, Kai; et al.
Abstract: Hypoxia is a hallmark of the tumor microenvironment (TME) that promotes tumor development and metastasis. Photodynamic therapy (PDT) is a promising strategy in the treatment of tumors, but it is limited by the lack of oxygen in TME. In this work, an O2 self‐supply PDT system is constructed by co‐encapsulation of chlorin e6 (Ce6) and a MnO2 core in an engineered ferritin (Ftn), generating a nanozyme promoted PDT nanoformula (Ce6/Ftn@MnO2 ) for tumor therapy. Ce6/Ftn@MnO2 exhibits a uniform small size (15.5 nm) and high stability due to the inherent structure of Ftn. The fluorescence imaging and immunofluorescence analysis demonstrate the pronounced accumulation of Ce6/Ftn@MnO2 in the tumors of mice, and the treatment significantly decreases the expression of hypoxia‐inducible factor (HIF)‐1α. The Ce6/Ftn@MnO2 nanoplatform exerts a more potent anti‐tumor efficacy with negligible damage to normal tissues compared to the treatment with free Ce6. Moreover, the weak acidity and the presence of H2 O2 in TME significantly enhances the r1 relativity of Ce6/Ftn@MnO2, resulting in a prominent enhancement of MRI imaging in the tumor. This bio‐mimic Ftn strategy not only improves the in vivo distribution and retention of Ce6, but also enhances the effectiveness and precision of PDT by TME modulation. Abstract : An O2 self‐supply PDT system is constructed by co‐encapsulation of chlorin e6 (Ce6) and MnO2 cores in an engineered ferritin (Ftn), generating a nanozyme promoted PDT nanoformula (Ce6/Ftn@MnO2 ) for tumor therapy. Moreover, the anti‐tumor effect and r 1 relativity of Ce6/Ftn@MnO2 can be significantly enhanced by the tumor microenvironment with weak acidity and H2 O2 .